A simple, rapid, high-fidelity and cost-effective PCR-based two-step DNA synthesis method for long gene sequences - Xiong, Ai-Sheng (Oxford University Press, 2004)
Chemical synthesis of DNA sequences provides a powerful tool for modifying genes and for studying gene function, structure and expression. Here, we report a simple, high-fidelity and cost-effective PCR-based two-step DNA synthesis (PTDS) method for synthesis of long segments of DNA. The method involves two steps. (i) Synthesis of individual fragments of the DNA of interest: ten to twelve 60mer oligonucleotides with 20 bp overlap are mixed and a PCR reaction is carried out with high-fidelity DNA polymerase Pfu to produce DNA fragments that are ∼500 bp in length. (ii) Synthesis of the entire sequence of the DNA of interest: five to ten PCR products from the first step are combined and used as the template for a second PCR reaction using high-fidelity DNA polymerase pyrobest, with the two outermost oligonucleotides as primers. Compared with the previously published methods, the PTDS method is rapid (5–7 days) and suitable for synthesizing long segments of DNA (5–6 kb) with high G + C contents, repetitive sequences or complex secondary structures. Thus, the PTDS method provides an alternative tool for synthesizing and assembling long genes with complex structures. Using the newly developed PTDS method, we have successfully obtained several genes of interest with sizes ranging from 1.0 to 5.4 kb.